Genotipagem do HIV-1 no Pará em pacientes experimentando falha terapêutica antirretroviral - LOPES, Carmen Andréa Freitas (Universidade Federal do Pará, 2013)
Suppressive antiretroviral therapy significantly reduces morbidity and mortality related to HIV, but the emergence of resistant virus may limit the success of treatment. The objective of this study describe, in HIV / AIDS experiencing failure with antiretroviral therapy, in state of Pará, the prevalence of mutations in reverse transcriptase and protease enzymes of HIV-1 and correlate them to resistance to antiretrovirals. A descriptive, retrospective crosssectional data obtained in the Reference Unit Specialized in Special Infectious and Parasitic Diseases from Belem-Pará, profile of patients with laboratory evidence of treatment failure. This sample was represented by genotyping of fifty patients from January 2004 to December 2005. Inclusion criteria were: adherence to therapy prior to genotype, treatment failure, viral resistance profile to antiretroviral therapy and be patient of public health. We described the demographic population profile of antiretroviral therapy prior to genotyping, long known HIV infection, quantitative profile of CD4 + and viral load, in addition to genotype testing performed. The predominant resistance found in patients living in Belém (72%), males (90%) and aged 30 to 49 years old. The highest rates of mutations in reverse transcriptase of HIV-1 were: 214F (86%), 184V (76%), 215FY (56%), 211K (48%), 219QEN, 67N and 103N (42% each), 41L (32%), 70R (28%) and 210W (20%). In 46IL protease (38%), 90M (32%) and 82AFT (20%) were most prevalent among the major replacements and, among the secondary, 63P (74%), 93LM (52%), 10FIV (48%), and 35D (46%) predominated. Was attributed to selective pressures these mutations most commonly used antiretrovirals: 3TC, AZT, D4T, DDI, EFV, IDV, NFV, RTV and SQV. The use of multiple antiretroviral regimens, boosted the prevalence of these mutations, with an impact within the classes in which there was 32% complete resistance to one class, 22% two classes and 4% to three classes of antiretrovirals. We conclude that patients exposed to HAART only prior to genotyping compared to those exposed to more than one HAART had a lower prevalence of resistance to antiretrovirals, with the possibility of rescue therapy with antiretrovirals assets available at the time that was the minority however.